CONTRIBUTION A L’ETUDE TEMPORELLE DU ZOOPLANCTON DE QUELQUES ZONES HUMIDES TEMPORAIRES (MARES) DE LA REGION DE SOUK AHRAS - Harkat Hadjer; Aouassa Safia (My University, 2015)
Chemical and biological characterization of seven physico temporary pools (Bourgas1, Bourgas 2, Majan Bouhssane, Ain Senyour, Loumajan, Ma Lahmar and El Bateha). in the region of Souk Ahras in was made during a wet period between December 2014 and May 2015. The study shows that the water physico-chemistry makes the difference between the ponds of the region; to Majan Bouhssan the chlorides records the highest values while Bourgas 1 and 2 are sulphates. The inventory of zooplankton temporal fluctuations watches The copepods are present with three levels; Herpacticoide, cyclopoid and Calanoides whose species Diaptomus Cyaneus a wide distribution in the study area. The Cladocera prefer ponds conductivity student (Bourgas 1 and 2 and Majen Bouhssan. Ostracods appear the most during the hot period and finally anostracans are very scarce is represented by a single species Chirocephalus Diophantus. -------------------------------------------------------------------------------------- ان الخصائص الفيزيائية ,الكيميائية والبيولوجية للسبع برك المؤقتة (بورقاس1,بورقاس2,ماجن بوحصان,عين سنيور,لوماجن,ما لحمرو البطحة.)في منطقة سوق اهراس,خلال الفترة الرطبة بين ديسمبر2014وماي2015.هذه الدراسة بينت ان الحالة الفيزيائية و الكيميائية للماء تجعل الفرق بين برك المنطقة,حيث ان نسبة الكلور المرتفعة سجلت في ماجن بوحصان,بينما وجد الكبريت بنسب عالية في بورقاس1و2 . اما الجرد للعوالق الحيوانية والتغيرات الزمنية يوضح بان مجدافيات الارجل مثلت بثلاثة رتب: Herpacticoide, cyclopoide و Calanoide. النوع Diaptomus Cyaneus ذا انتشار واسع في منطقة الدراسة. الكلادوسير دائمة الحضور في الفترة الحارة. واخيرا الانوستراسي قليلة التواجد وقد مثلت بنوع واحد و هو: Chirocephalus Diaphanus . -------------------------------------------------------------------------------------------- La caractérisation physico chimique et biologique de sept mares temporaires (Bourgas 1, Bourgas 2, Madjen Bouhssane, Ain Senyour, Loumadjen , Ma Lahmar et El Bateha) de la région de Souk Ahras à été effectué au cours d’une période humide entre décembre 2014 et mai 2015. Cette étude montre que la physicochimie des eaux fait la différence entre les mares de la région ; à Majen Bouhssan les chlorures enregistres les valeurs les plus élèves alors que à Bourgas 1 et 2 c’est les sulfates. L’inventaire de zooplancton ainsi les fluctuations temporelles montres que Les Copépodes sont présent avec trois ordres ; Herpacticoide, Cyclopoide et Calanoides dont l’espèce Diaptomus Cyaneus à une large distribution dans la région d’étude. Les Cladocères préfères les mares à conductivité élève (Bourgas 1 et 2 et à Majen Bouhssan. Les Ostracodes apparaissent le plus durant la période chaude et enfin les Anostracés sont très peu abondant est sont représentés par une seule espèce Chirocephalus Diaphanus